Perlindungan Hukum Pendapatan Bersih Royalti sebagai Harta Bersama (Studi Putusan Nomor 16/Pdt.G/2024/PTA.JK) - Rahayu, Hesni; Trihastuti, Nanik (Universitas Syiah Kuala, 2025)
This study was motivated by the increasing number of divorce disputes involving the division of intangible assets, particularly net income from copyright royalties, which are not explicitly regulated in Indonesian legislation. Royalties, as the economic proceeds of intellectual property, are recurring and high in value, giving rise to legal issues when they are acquired during marriage. This study aims to analyze the form of legal protection for net royalty income as joint property and how the judge's considerations in Decision Number 16/Pdt.G/2024/PTA.JK position it within the framework of family law. The research method used is normative juridical with a legislative and case approach, using secondary data through a qualitative analysis of literature. The results of the study show that royalties generated during marriage are categorized as joint property based on Article 35 paragraph (1) of Law Number 1 of 1974 and Article 91 of the Compilation of Islamic Law. The Jakarta Religious High Court ruling confirms that 50% of the total net royalty income is part of joint property because it contributes to the welfare of the household. In conclusion, legal protection of royalties as joint property is an effort to realize the principles of justice and legal certainty in the distribution of post-marital wealth, while strengthening the integration between intellectual property law and family law.